Internasionalisasi Bahasa Indonesia: Upaya BIPA Dan Fenomena Penurunan Minat Bahasa Indonesia di Australia Tahun 2020-2024 - Fithriana, Arin; Putri Karamina, Fadiah (GLOBAL INSIGHT JOURNAL, 2024)
Internationalization of Bahasa Indonesia conducted to build a positive image of the country. One of the ways to achieve this is by implementing the Indonesian Language for Foreign Speakers (BIPA) program. Australia is one of the countries that has many BIPA teaching institutions. However, there is a fluctuating phenomenon that tends to decrease the interest in learning Indonesian in Australia. Therefore, this research aims to find out how Indonesia's efforts to internationalize Indonesian language in Australia in 2020-2024 through the BIPA program. To achieve this goal, this research uses a qualitative approach in its analysis and will explain the results obtained in the form of descriptions using the liberalism paradigm with the concept of Internationalization and Nation Branding. The results show that the use of diaspora, the implementation of cultural and language promotion programs, the use of digital media and technology have been carried out by Indonesia. Seeing the fluctuating phenomenon tends to decrease interest in learning Indonesian that occurs in Australia. So the Internationalization of Indonesian language is still a form of potential soft power, so that it is important for the state to continue to make communication efforts in nation branding which will then gradually be able to build the image of the country. Keywords: BIPA, Nation Branding, Indonesia, Australia, Cooperation